Utilization of Microvisco-amylograph to Study Flour, Dough and Bread Qualities of Hydrocolloid/Flour Blends - Hammed, Ademola Monsur; Ozsisli, Bahri; Simsek, Senay (Taylor and Francis, 2016)
Changes in functionality of wheat flour blended with hydrocolloids (alginate, locust bean gum, guar gum and xanthan) were investigated. Microvisco-amylograph (MVAG) and flour quality analyses were conducted and showed significant (P<0.05) differences among samples. Correlation of MVAG values with other parameters showed that MVAG parameters (final viscosity, setback, breakdown, etc.) showed significant (P<0.05) correlation with other parameters. MVAG breakdown was significantly (P<0.05) and positively correlated with dough strength and loaf volume. MVAG end of cooling, final viscosity, setback and breakdown were identified as valuable for determination of flour, dough and bread qualities as impacted by addition of hydrocolloids.